Single level anterior cervical discectomy and fusion for cervical disc herniation in a professional soccer player - Casagrande, J.; Zoia, C.; Clerici, G.; Uccella, L.; Tabano, A. (The Journal of Sports Medicine and Physical Fitness, 2016)
A 29-year old midfielder playing professional soccer complains of neck and right shoulder pain without apparent cause. A cervical MR shows disc herniation between C4 and C5 compressing 5th nerve root. The patient undergoes surgical discectomy plus interbody fusion with autologous bone and plate fixation with unicortical screws. No surgical complication is observed and after four weeks of rest, the patient begins a specific rehabilitation program including Tecar Therapy sessions and manual passive physical therapy for six weeks. Two times a week he attends hydrokinesis sessions. After eight weeks the athlete can restart working directly on soccer field and after less than four months he is back on an official competition